Mixed Adsorption Mono- and Multilayers of ß-Lactoglobulin Fibrils and Sodium Polystyrene Sulfonate - A. G. Bykov; G. Loglio; R. Miller; E. A. Tsyganov; Z. Wan; B. A. Noskov (Colloids and Interfaces, 2024)
The formation of beta-lactoglobulin (BLG)/sodium polystyrene sulfonate (PSS) complexes decelerates the change in the surface properties of the mixed solutions with the surface age and increases the steady-state dilational surface elasticity in a narrow PSS concentration range. At the same time, the changes in the surface properties are accelerated in the dispersions of BLG fibrils with and without PSS due to the influence of small peptides coexisting with fibrils. A decrease in the peptide concentration as a result of the dispersion purification leads to slower changes in the surface properties at low PSS concentrations. The increase in the polyelectrolyte concentration results in an increase in the steady-state surface elasticity due to the fibril/PSS complex formation and in very slow changes in the surface properties if the polyelectrolyte exceeds a certain critical value. The latter effect is a consequence of the formation of large aggregates and of an increase in the electrostatic adsorption barrier. The consecutive adsorption of BLG fibrils and PSS leads to the formation of regular multilayers at the liquid–gas interface. The multilayer properties change noticeably with an increase in the number of layers from four to six in agreement with previous results on the multilayers of PSS with an oppositely charged synthetic polyelectrolyte, presumably due to the heterogeneity of the first PSS layer. The dynamic elasticity of the multilayers approaches 250 mN/m, indicating that they can effectively stabilize foams and emulsions.